Opinions of primary school principals in Bunia City (DRC) on the establishment of infirmaries within their schools - Justin, NDJABU; Mukandu, Basua Babintu Leyka; Bura, Pulunyo Cajetan Mauricex; Alworong’a , Opara Jean Pierre (Orapuh Journal, 2025)
Introduction This study presents the different opinions of the Heads of Primary Schools in the City of Bunia regarding the establishment of an infirmary within their schools. Purpose The objectives of this study are to: identify their opinions on the long- and short-term benefits of establishing a school infirmary in primary schools; identify the challenges or obstacles identified by the heads of primary schools for the establishment of an infirmary; identify the proposals or suggestions of the heads of establishments for the establishment of an infirmary in schools; and describe the opinions of the heads of establishments regarding the management of an infirmary in primary schools. Methods The ethnographic method was used for this study. Data were collected through individual semi-structured interviews and were subjected to inductive analysis of the thematic content. Results This study revealed that the lack of financial resources is the major challenge in setting up an infirmary. Most heads of establishments favour the establishment of an infirmary in primary schools with the involvement of public authorities. The preferred model for managing an infirmary is collaboration between the permanent nurse, the head of the establishment, and the State, according to most heads of establishments. Integrating medical care is essential for saving students’ lives. Most respondents confirm the ineffectiveness of medical care in schools due to the lack of required resources. Conclusion Raising awareness among the leaders of primary schools in the City of Bunia about the establishment of infirmaries within primary schools is necessary in order to effectively manage health emergencies.